Fulminant infective endocarditis with toxin-negative Corynebacterium diphtheriae in people with substance use experiencing homelessness, England, 2024 to 2025 - Patel, Tara; Anwar, Tasnim; Mavrogiorgou, Eleni; Utjesanovic, Natasa; Aryee, Anna; Litt, David J; D’Aeth, Joshua C.; Primus, Christopher; Das, Satya; Karogiannis, Nikolaos; Paranthaman, Karthik; Amirthalingam, Gayatri; et al. (Euro surveillance : bulletin européen sur les maladies transmissibles, 2025)
Between July 2024 and January 2025, five male patients in their early 20s to early 50s were confirmed with infective endocarditis associated with non-toxigenic Corynebacterium diphtheriae in England. Three were known to have experienced homelessness. All five used non-intravenous recreational drugs. Disease progression was rapid, four patients required surgical intervention, one died. Whole-genome sequencing and multilocus sequence type (MLST) analysis identified four individuals as ST559. Clinicians and substance use services have been alerted and enhanced surveillance implemented. A prevalence study is planned.